Early mandated social distancing is a strong predictor of reduction in peak daily new COVID-19 cases. (January 2021) - Qureshi, A.I.; Suri, M.F.K.; Chu, H.; Suri, H.K.; Suri, A.K.
Abstract: Objectives: Mandated social distancing has been applied globally to reduce the spread of coronavirus disease 2019 (COVID-19). However, the beneficial effects of this community-based intervention have not been proven or quantified for the COVID-19 pandemic. Study design: This is a regional population-level observational study. Methods: Using publicly available data, we examined the effect of timing of mandated social distancing on the rate of COVID-19 cases in 119 geographic regions, derived from 41 states within the United States and 78 other countries. The highest number of new COVID-19 cases per day recorded within a geographic unit was the primary outcome. The total number of COVID-19 cases in regions where case numbers had reached the tail end of the outbreak was an exploratory outcome. Results: We found that the highest number of new COVID-19 cases per day per million persons was significantly associated with the total number of COVID-19 cases per million persons on the day before mandated social distancing (β = 0.66, P < 0.0001). These findings suggest that if mandated social distancing is not initiated until the number of existing COVID-19 cases has doubled, the eventual peak would result in 58% more COVID-19 cases per day. Subgroup analysis on those regions where the highest number of new COVID-19 cases per day has peaked showed increase in β values to 0.85 ( P < 0.0001). The total number of cases during the outbreak in a region was strongly predicted by the total number of COVID-19 cases on the day before mandated social distancing (β = 0.97, P < 0.0001). Conclusions: Initiating mandated social distancing when the numbers of COVID-19 cases are low within a region significantly reduces the number of new daily COVID-19 cases and perhaps also reduces the total number of cases in the region. Highlights: The number of coronavirus disease 2019 (COVID-19) cases at the time of mandated social distancing in a region is a strong predictor of peak daily new cases. Early mandated social distancing significantly reduces the number of daily new COVID-19 cases in the region. Early mandated social distancing also likely significantly reduces the total number of COVID-19 cases in the region.